Estimating density of Sunda Scops Owl using the call playback method - Pilla, Phillcaine; Puan, Chong Leong; Zolkanain, Nornajmi Hanis; Hussin, Mohamed Zakaria (Faculty of Forestry, Universiti Putra Malaysia, 2013)
Owls are an important predator in the food web and their density may reflect their prey populations in an ecosystem. However, the density of owls in a forest is often very difficult to estimate. The objective of the study was to estimate the density of Sunda Scops Owl (Otus lempiji) at Ayer Hitam Forest Reserve, Puchong, Selangor using the call playback method. Nocturnal survey was conducted at 60 sampling points that were located 150-170 m apart. At each point, a 10-min silent listening was made before the broadcasting of owl calls for 2 min. Preliminary results indicated that the density of the owls was five individuals per 10 ha based on silent listening and two birds per 10 ha using the call playback method. The results implied that the owl density in the forest estimated based on the call playback method may be different as compared to that obtained through silent listening. Such a difference may be due to the behaviour of the owls in responding to their call during the breeding and non-breeding seasons.